Effect of pH on carbon steel corrosion in the presence of a sour medium (Superficies y Vacío, 2012)
The analysis of electrochemical behaviour of carbon steel immersed in a sour water of the petroleum industry, varying the pH, was studied. Different techniques used show the presence of three important corrosion stages: adsorption, species diffusion and localised corrosion. MEB analysis showed the presence of corrosion products only at pH 8.5, while in all the pH tested there are cavities or pitting. The EDS study confirms the presence of oxygen, calcium and chlorides at pH 8.5, where the corrosion products are present.